The taming of prices: Framing and fighting inflation in the second half of the twentieth century in Argentina - Heredia, Mariana Laura (2019)
Our argument is that, if we suspend disciplinary distinctions, inflation reveals two contrasting modes of representing the economy. At least in Argentina, the growing concern about inflation is related to the consolidation of price indexes and the rise of economists asprimary actors in public and political life. Numbers and experts did not just add new terminology and interpreters to inflation analyses, they completely changed the way societies and authorities act to tame price rises.